Performing Auspiciousness: Periya Melam Music in South Indian Marriage Ceremony - Yoshitaka Terada (Wacana Seni Journal of Arts Discourse, 2005)
During the months considered appropriate for marriage ceremony, any locality in Tamil Nadu is filled with the music of the Periya Melam ensemble. One may hear its sound flowing from a marriage hall early in the morning, or encounter an ensemble at night leading the procession of a bridegroom or bride decorated with bright colored garlands. People are dressed up with expensive silk garments, and the atmosphere is exuberant and jovial. Going through a densely populated area such as the Mylapore or T-Nagar sections of Chennai (formerly Madras), one may experience such an event almost at every block.